Earlier or Later: A General Equilibrium Analysis of Bringing Forward an Already Announced Tax Reform - Josef Honerkamp; Stefan Moog; Bernd Raffelhüschen (Albert-Ludwigs-Universität Freiburg, Institut für Finanzwissenschaft, 2004)
The German Income Tax Reform 2000, which announced a reduction in income tax rates to be implemented in a series of three stages, was welcomed by the public as a step towards unleashing lurking growth potentials. Nonetheless, in the course of the year 2001 a dispute arose, centering around the question, whether or not the later stages of the German Income Tax Reform should be brought forward. The present paper assesses the welfare and macroeconomic consequences of the German Income Tax Reform in the scope of a simplified DGE model of the Auerbach-Kotlikoff type and deals explicitly with the issue of bringing forward an already announced tax reform. Besides evaluating the considered fiscal policy options in terms of their (social) welfare implications we touch on the political economy aspects of implementing a tax reform.
urn:nbn:de:bsz:25-opus-18579
Keywords: H30; H24; E62; D58; 330; German Tax Reform; early tax reform; overlapping generations; DGE model; Einkommensteuer; Steuerreform; Ankündigungseffekt; Overlapping Generations; Allgemeines Gleichgewicht; Wohlfahrtseffekt; Schätzung; Theorie; Deutschland